2018
DOI: 10.1097/icl.0000000000000468
|View full text |Cite
|
Sign up to set email alerts
|

Corneal and Anterior Chamber Morphology in Human Immunodeficiency Virus-1–Infected Patients Without Opportunistic Infections

Abstract: Corneal density, CECD, ACV, and ACD showed significant correlation with age in HIV-1-infected patients. Further studies are needed to show whether ocular parameters may serve as useful tools to monitor HIV-related accelerated aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Cetin and colleagues (2018) undertook a comprehensive study of corneal and anterior chamber morphology but found no significant differences in a range of anterior ocular structural measures (e.g. corneal endothelial cell density, corneal thickness and volume, anterior chamber depth and volume) between HIV-positive individuals and healthy controls [25], despite a previous study demonstrating increased risk of corneal endothelial cell polymegathism in HIV-infected individuals [26].…”
Section: Discussionmentioning
confidence: 99%
“…Cetin and colleagues (2018) undertook a comprehensive study of corneal and anterior chamber morphology but found no significant differences in a range of anterior ocular structural measures (e.g. corneal endothelial cell density, corneal thickness and volume, anterior chamber depth and volume) between HIV-positive individuals and healthy controls [25], despite a previous study demonstrating increased risk of corneal endothelial cell polymegathism in HIV-infected individuals [26].…”
Section: Discussionmentioning
confidence: 99%